Molecular signatures associated with diuron exposure on rat urothelial mitochondria - Lima, Thania Rios Rossi [UNESP] (2022)
Diuron, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, is a worldwide used herbicide whose biotransformation gives rise to the metabolites, 3-(3,4-dichlorophenyl)-1-methylurea (DCPMU) and 3,4-dichloroaniline (DCA). Previous studies indicate that diuron and/or its metabolites are toxic to the bladder urothelium of the Wistar rats where, under certain conditions of exposure, they may induce successively urothelial cell degeneration, necrosis, hyperplasia and eventually tumors. The hypothesis was raised that the molecular initiating event (MIE) of this Adverse Outcome Pathway is the mitochondrial toxicity of those compounds. Therefore, this study aimed to investigate in vitro the metabolic alterations resulting from urothelial mitochondria isolated from male Wistar rats exposure to diuron, DCPMU and DCA at 10 and 100 µM. A non-targeted metabolomic analysis using mass spectrometry showed discriminative clustering among groups and alterations in the intensity abundance of membrane-associated molecules phosphatidylcholine, phosphatidylinositol and phosphatidylserine, in addition to methylhexanoyl-CoA and, particularly for diuron 100 µM, dehydro-L-gulonate, all of them involved in critical mitochondrial metabolism. Collectively, these data indicate the mitochondrial dysfunction as an MIE that triggers cellular damage and death observed in previous studies.